Modeling and Experimental Studies on Water Spray Cooler for Commercial Photovoltaic Modules - Xuan Cuong Ngo; Nhu Y Do; Quoc Vuong Dang (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
This paper presents modeling and experimental studies on water spray coolers for commercial photovoltaic modules. This paper has compared the energy yield of four photovoltaic commercial modules that were installed with a fixed tilt angle being equal to the local latitude in central Vietnam, including one photovoltaic module using a water spray cooler and three photovoltaic modules without cooling. Experimental results on sunny days have been shown that the energy yield difference between four PV modules under the same working condition is lower than 1%. In addition, on sunny days when the set working temperature of the water spray cooler is 45 °C, the average improvement efficiency of a photovoltaic module using a water spray cooler compared to three reference photovoltaic modules is 2.64%, 3.83%, and 6.18%, for an average of 4.22%. A simple thermal–electrical model of a photovoltaic module with a water spray cooler has been developed and tested. The normalized root mean square error between simulated and measured results of photovoltaic module power output on a sunny day without cooling and with water spray cooler reached 6.5% and 8.5%, respectively. The obtained results are also demonstrated that the reasonableness of the simple thermal–electrical model of the photovoltaic module with water spray cooler and the feasibility of a cooling system is improved to increase the efficiency of the photovoltaic module. In addition, they can be considered as a basis for new experimental models in the future.